2015
DOI: 10.1590/abd1806-4841.20153625
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis associated with paretic neurosyphilis mimicking Reiter’s syndrome in HIV-infected patients

Abstract: HIV/syphilis co-infection is common because both conditions affect similar risk groups. HIV interferes with the natural history of syphilis, which often has atypical clinical features and nervous system involvement in the early stage of disease. We report the case of an HIV-positive patient with secondary syphilis, scaling palmoplantar keratoderma, scrotal eczema, balanitis and urethritis mimicking Reiter’s syndrome. Immunohistochemistry using polyclonal antibodies against Treponema pallidum revealed the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Scrotal eczema, associated with the typical manifestation of erythematous macules/papules of the palms and soles, was another atypical manifestation of SS in our series; to the best of our knowledge, this type of lesion was previously reported only in four cases, two of which were HIV-seropositive [ 51 , 52 , 53 ]. Although in our patients with scrotal eczema histopathology and immunohistochemistry for a polyclonal antibody against T. pallidum were not performed, the concomitant diagnosis of syphilis in the sexual partner in one case and personal history of several unprotected sexual intercourses in the other, together with the complete resolution of eczema after specific antibiotic therapy, suggested that these lesions were atypical manifestations of syphilis.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Scrotal eczema, associated with the typical manifestation of erythematous macules/papules of the palms and soles, was another atypical manifestation of SS in our series; to the best of our knowledge, this type of lesion was previously reported only in four cases, two of which were HIV-seropositive [ 51 , 52 , 53 ]. Although in our patients with scrotal eczema histopathology and immunohistochemistry for a polyclonal antibody against T. pallidum were not performed, the concomitant diagnosis of syphilis in the sexual partner in one case and personal history of several unprotected sexual intercourses in the other, together with the complete resolution of eczema after specific antibiotic therapy, suggested that these lesions were atypical manifestations of syphilis.…”
Section: Discussionmentioning
confidence: 46%
“…There are several possible mechanisms responsible for the annular shape: lesions simply form at a site and then spread radially; a lesion can have a centrifugal spread by extension along a plane in the skin; or an inflammatory process may extend along a vessel and, because the vessels are arranged in a grid-like network, the clinical result is a figurate lesion [50]. Scrotal eczema, associated with the typical manifestation of erythematous macules/papules of the palms and soles, was another atypical manifestation of SS in our series; to the best of our knowledge, this type of lesion was previously reported only in four cases, two of which were HIV-seropositive [51][52][53]. Although in our patients with scrotal eczema histopathology and immunohistochemistry for a polyclonal antibody against T. pallidum were not performed, the concomitant diagnosis of syphilis in the sexual partner in one case and personal history of several unprotected sexual intercourses in the other, together with the complete resolution of eczema after specific antibiotic therapy, suggested that these lesions were atypical manifestations of syphilis.…”
Section: Discussionmentioning
confidence: 48%